Italian (ACME, 2020)
Antonio Brocardo is remembered for being entered into controversy with Pietro Bembo, arousing public indignation. The ancient sources on the life of Bembo described him like a madman intent on wanting to destroy what he could not well understand. But there is, however, a huge gap: the tradition wants him opposed the Bembo’s doctrine, and yet his rhymes does not seem to differ so flagrantly from the canon of Bembo (as stated in numerous literary stories.The article aims to clarify - through a reasoned use of stylometry - the real reasons for the controversy between Bembo and Brocardo, corroborating previous philological conjectures. The analysis of the different usus scribendi of the two poets were conducted in relation to the vulgar production of Petrarch.We would like here to demonstrate how the stylometry can be used as litmus test, to confirm or reject hypothesis of philological work.